Magnetic Resonance Imaging Template to Standardize Reporting of Evacuation Disorders - Vittorio Piloni; Tiziana Manisco; Marco Fogante (Journal of Imaging)
Magnetic resonance (MR) defecography, including both static and dynamic phases, is frequently requested by gastroenterologists and colorectal surgeons for planning the treatment of obstructive defecation syndrome and pelvic organ prolapse. However, reports often lack key information needed to guide treatment strategies, making management challenging and, at times, controversial. It has been hypothesized that using structured radiology reports could reduce missing information. In this paper, we present a structured MR defecography template report that includes nine key descriptors of rectal evacuation. The effectiveness and acceptability of this template are currently being assessed in Italy through a national interdisciplinary study.